Effectiveness and Function of Dietary and Medical Iron Interventions in Treating Iron-Deficiency Anemia: A Systematic Review: Dietary and Medical Iron Interventions in Iron-Deficiency Anaemia - Ali, Akbar; Khalid, Maham; Sammar, Kinza; Fida, Najma; Asmatullah, Aamir; Anwar, Saadia (Pakistan Journal of Health Sciences, 2025)
Iron-deficiency anaemia is a widespread nutritional disorder affecting individuals across all age groups, particularly children, pregnant women, and those with chronic illnesses. It arises due to insufficient dietary intake, impaired absorption, or increased iron loss, reducing haemoglobin and oxygen-carrying capacity. Objectives: To compare the effectiveness of dietary and medical iron interventions in preventing and treating iron-deficiency anaemia across different populations. Methods: A comprehensive search was conducted in PubMed, Scopus, Google Scholar, and Cochrane Library for studies published between 2017 and February 2025. Eligible studies included randomized controlled trials and clinical trials evaluating iron interventions in individuals with or at risk of iron-deficiency anaemia. Primary outcomes included changes in haemoglobin, serum ferritin, total body iron, and anaemia prevalence. Results: Both dietary and medical interventions were effective in improving iron status. Iron-fortified foods, micronutrient powders, and bioavailability enhancers such as vitamin C and probiotics were cost-effective for population-level prevention. Medical therapies, including oral and intravenous iron, provided rapid correction in individuals with moderate to severe anaemia. Adherence and long-term sustainability remained key challenges across both approaches. Conclusions: It was concluded that integrating dietary strategies with medical interventions offers the most effective approach for managing iron-deficiency anaemia. Future research should focus on enhancing adherence, improving iron bioavailability, and personalizing treatment based on individual needs.